2023
DOI: 10.3390/life13020482
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondriomics of Clarias Fishes (Siluriformes: Clariidae) with a New Assembly of Clarias camerunensis: Insights into the Genetic Characterization and Diversification

Abstract: The mitogenome of an endemic catfish Clarias camerunensis was determined from the Cameroon water. This circular mitogenome was 16,511 bp in length and comprised 13 protein-coding genes, 2 ribosomal RNAs, 22 transfer RNAs, and a single AT-rich control region. The heavy strand accommodates 28 genes, whereas the light strand is constituted by ND6 and eight transfer RNA (tRNA) genes. The C. camerunensis mitochondrial genome is AT biased (56.89%), as showcased in other Clarias species. The comparative analyses reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…A comparative study of the other two Coptodon mitogenomes revealed that the AT skew varied from 0.027 to 0.028, and the GC skew ranged from 0.299 to 0.306 ( Table 2 ). A similar pattern of the nucleotide composition and AT biases were reported in previously characterized fish mitogenomes [ 90 , 91 ]. The genetic diversity detected in Coptodon mitogenomes could be related to their evolutionary process and energy metabolism, as demonstrated in other fish [ 92 ].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…A comparative study of the other two Coptodon mitogenomes revealed that the AT skew varied from 0.027 to 0.028, and the GC skew ranged from 0.299 to 0.306 ( Table 2 ). A similar pattern of the nucleotide composition and AT biases were reported in previously characterized fish mitogenomes [ 90 , 91 ]. The genetic diversity detected in Coptodon mitogenomes could be related to their evolutionary process and energy metabolism, as demonstrated in other fish [ 92 ].…”
Section: Resultssupporting
confidence: 83%
“…zillii mitogenomes contained tandem repeats. The conserved block locations (CSBD, CSBI, CSBII, and CSBIII) were determined to be comparable in both C. camerunensis and C. zillii , as documented in other teleost fishes [ 90 , 91 , 97 ]. The length of the CSBII block was the longest (52 bp) when compared to the other blocks, which were CSBD (27 bp), CSB-I (41 bp), and CSBIII (43 bp).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Comparative analysis of P. erumei mitogenomes demonstrated an AT skew range of 0.076 to 0.077, and a GC skew range of −0.323 to −0.328 (Table 2). This consistent nucleotide composition pattern and AT bias were also observed in other previously described fish mitogenomes [60,61]. The genetic variations identified within the Psettodes mitogenome may be tied to their evolution-ary progression and energy metabolism, echoing findings in other fish species [62].…”
Section: Mitogenomic Structure and Organizationsupporting
confidence: 85%
“…In addition, several small- to large-scale DNA barcoding attempts have been made to illuminate the genetic diversity of catfishes around the world, including in Africa [ 35 , 36 , 37 , 38 ]. A recent study generated the first mitochondrial genome of C. camerunensis and elaborated the diversification of Clarias species in Africa and the Asian continent [ 39 ].…”
Section: Introductionmentioning
confidence: 99%